(untitled) (Jurnal Online Pertanian Tropik, 2022)
Sweet corn is a crop has a very good nutrient and tastes sweet and Calsium influenced contain. Ultisol is one of the soil that spreaded vastly in Indonesia, up to 25% of Indonesian total terrestrial area. Ultisol is an acidic soil, hence clacification can be applied to deal with it. The purpose of this research was to determine the growth response of sweet corn in two sources of calcium nutrients application to Ultisol soil. This research was conducted in the gauze of the Faculty of Agriculture, University of Sumatera Utara with an altitude of ± 32 m above sea level starting from October 2017 to December 2017. This research used a Non Factorial Completely Randomized Design with 7 treatments and 4 repetition, the treatment of which was calcium nutrient, shell egg (9.22 g / 15 kg soil), eggshell (13.84 g / 15 kg soil), eggshell (18.45 g / 15 kg soil), dolomite 1 x Aldd (equivalent to 9.22 g / 15 kg of soil), dolomite 1.5 x Aldd (equivalent to 13.84 g / 15 kg of soil), dolomite 2 x Aldd (equivalent to 18.45 g / 15 kg of soil). The results showed that the two sources of calcium nutrients (eggshell or dolomite) applications had no significant effect on plant height, leaf number, stem diameter, canopy and root wet weight, and canopy and root dry weight.